International Corporate Finance 10/ed - Madura (New Delhi : Cengage Learning, 2010)
International corporate finance, 10e, indian edition builds on fundamental principles of corporate finance to provide the information and insights you need to succeed in today's dynamic global business environment. This thorough text includes a detailed introduction to the world of international finance, in which multinational corporations continue to expand and play an increasingly important role in global commerce. The text then focuses on a wide range of managerial topics from a corporate perspective, combining in-depth coverage of essential financial theory with a strong emphasis on hands-on, real-world applications. Known for its reader-friendly style and clear explanations, international corporate finance, 10e, indian edition gives you the tools to understand and manage within the exciting field of international finance.
Unabridged.